MIMOS Berhad: A case study on innovation and commercialization - Yusoff, Rushami Zien; Mohtar, Shahimi; Ramli, Azahari; Hassan, Mohamad Ghozali; Halim, Helmi (Universiti Utara Malaysia, 2012)
At this point, the acculturation of innovation and commercialization in Malaysia is still in development stage.The same situation happens in the context of development of national ICT sector is still lagging behind. If developed countries such as Japan, Korea, China and European countries are taken into account, Malaysia is still far lagging behind, especially in the ICT sector. This role is borne by MIMOS Berhad that is always looking for space in developing and promoting the development of innovations focuses on ICT sector. In line with the vision "To be a Premier Applied Research Center in Frontier Technologies", and the mission "To Pioneer Innovation Information & Communication Technologies Towards Indigenous growing Globally Competitive Industries", MIMOS Berhad is constantly evolving with many notable achievements.Staff and organizational restructuring in 2006, has seen a significant difference.This case study aims to analyze the strategy that plays a role in bringing high MIMOS Berhad to the extent that now.The results show that the strategies implemented in line with the vision and mission, right at the place and time of implementation, has a short-term strategies and long-term strategy, and have the confidence to achieve success.Strategies implemented taking into consideration the overall human resource development begins with an individual also give emphasis on competition globally.